Probiotic potential of and conjugated linoleic acid production by bacteria isolated chicken and ruminants - Yong, Su Ting (2013)
Conjugated linoleic acid (CLA) refers to fatty acids with 18-carbon and 2 conjugated double bonds in different positional and geometric configurations (C18:2). CLA can be normally found in ruminant meat, milk, cheese, dairy products, egg yolk and chicken. Dietary CLA intake by human is too low to exhibit health benefits such as anti-cancer, anti-inflammatory, anti-atherosclerosis, anti-obesity and modulation of immune system. Furthermore, the purity of CLA isomers is crucial for human health but the commercially available CLA was mostly produced by chemical synthesis which leads to the production of mix isomers of CLA. This can be achieved through bioproduction of CLA by bacteria and the increase of consumption of CLA enriched products by human. Therefore, the objectives of this study were to investigate the ability of bacteria isolated from ruminants, chicken, human milk and infant feces to produce CLA and to evaluate their probiotic characteristics and factors that affect the CLA production. In this study, 120 isolates were tested for the presence of catalase and Gram staining. A total of 69 isolates with catalase negative, Gram positive and grown on MRS medium under anaerobic condition were screened for CLA production. From the screening results, 18 isolates which isolated from cattle, deer and chicken have the ability to produce CLA from lactic acid (LA). The four highest CLA-producing bacteria were isolated from chicken and cattle. They were identified as Lactobacillus salivarius strain P2, Lactobacillus agilis strain P3, Enterococcus faecium strain P1 and Streptococcus equinus strain C3 based on molecular method and produced CLA concentration of 21.97, 31.08, 23.35 and 10.23 μg/ml,respectively. Lactobacillus salivarius strain P2, L. agilis strain P3, E. faecium strain P1 and S. equinus strain C3 consist of 60.65%, 66.90%, 49.77% and 52.01% of cis-9,trans-11 (c9, t11) CLA isomer and 39.35%, 33.10%, 50.23% and 47.99% of trans-10, cis-12 (t10, c12) CLA isomer, respectively. Reference strain, Lactobacillus reuteri ATCC 55739 produced CLA concentration of 122.45 μg/ml which consist of 89.24% of c9, t11 CLA isomer and 10.76% of t10, c12 CLA isomer. All bacteria tested were able to tolerate 0.3 % bile salts and pH 2.5 acidic condition. As compared to L.reuteri ATCC 55739, L. agilis strain P3 and L. salivarius strain P2 showed better acidic tolerance, resistant to two types of antibiotics tested, higher antimicrobial activity and ability to produce higher amount of lactic acid. All bacterial strains showed no bacteriocin production. Streptococcus equinus strain C3 was resistant to four types of antibiotic tested and E. faecium strain P1 was hemolytic positive bacteria. These characteristics have made these 2 strains not suitable as probiotic bacteria. The most efficient CLA production were obtained by 20% cell density in citrate buffer, pH 5.5 containing 1.0 mg/ml LA which were incubated at 30°C for 48 h with shaking at 120 rpm under aerobic condition. Under optimal reaction conditions, L. reuteri ATCC 55739 produced the highest concentration of CLA,280.75 μg/ml reaction mixture, followed by L. agilis strain P3 with 109.78 μg/ml reaction mixture and L. salivarius strain P2 with 84.58 μg/ml reaction mixture. The CLA isomers formed were majority c9, t11 CLA and minority t10, c12 CLA. Taking into account of the probiotic effect of bacteria, L. salivarius strain P2 and L. agilis strain P3 are more suitable to be probiotic for animals and to produce CLA extracellular. The findings in this study prompt further studies to be carried out to investigate the ability of bacteria to produce CLA and their probiotic effects in animal model.